Exploring Children’s Experiences Following Sport-Related Concussions: Identifying and Overcoming Emotional Challenges and Adversity Following Traumatic Brain Injury (TBI) - Mueller, Megan E.; Schmidt, Louis A.; Wright, Stephanie; Ali Raza, Insia; Patro, Gabriella; Rana, Mehwish; Volpe, Richard (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: To gain a better understanding of the emotional and mental experiences of child and adolescent athletes following a sport-related concussion, in order to better support these athletes throughout recovery.